The rarely encountered jewel beetle, Buprestis splendens Fabricius, 1775: First Korean record of the subgenus Cypriacis (Coleoptera: Buprestidae) with molecular insights - Kim, Donguk; Choi, Kwang Shik (Zootaxa, 2026)
This study reports the first record of the subgenus Cypriacis Casey, 1909 (Coleoptera: Buprestidae) of the genus Buprestis Linnaeus, 1758 from the Korean Peninsula, represented by the rarely encountered species Buprestis splendens Fabricius, 1775. This finding holds notable biogeographic significance, extending the known distribution of the subgenus. A redescription is provided, with photographs of the adult habitus and female genitalia, along with a key to known species and a checklist of Cypriacis. DNA barcoding of the mitochondrial cytochrome c oxidase subunit I (COI) gene substantiated the taxonomic position of B. splendens, providing the first molecular insight supporting its placement within the subgenus.